Hubungan Perilaku Gizi Seimbang dan Frekuensi Discretionary Foods dengan Status Gizi Remaja: Studi Cross-Sectional di SMA Negeri 4 Surabaya: Balanced Nutrition Behaviors and Discretionary Food Frequency in Relation to Adolescent Nutritional Status in Surabaya - Amany, Dhiaulhaq; Rahmah, Aulia; Muniroh, Lailatul (Universitas Airlangga, 2026)
Background: Adolescence is a vulnerable period for nutritional problems due to changes in nutritional needs and eating behaviors. In Surabaya, the prevalence of overweight among adolescents has reached 14.46%. One contributing factor is frequent consumption of discretionary foods, which are energy-dense and low in essential nutrients. Objectives: This study aims to analyze the relationship between balanced nutrition behaviors and the frequency of discretionary food consumption with adolescent nutritional status at SMA Negeri 4 Surabaya. Methods: An analytic observational study with a cross-sectional design was conducted among 83 students in the first and second grades of a higher secondary school, who were selected using proportional random sampling. Data were collected using a balanced nutrition behavior questionnaire, a Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ) to assess the Balanced Nutrition Index 3-60 (IGS3-60), and an FFQ to measure discretionary food consumption. Nutritional status was determined using BMI-for-age based on WHO-AnthroPlus. The obtained data were analyzed using Pearson and Spearman correlation tests. Results: Most respondents had poor balanced nutrition behavior (51.8%). Discretionary foods rich in added sugars, fats, and sugar–fat combinations were frequently consumed on a weekly basis. Significant associations were found between discretionary food consumption and nutritional status, including high added sugars (p-value=0.015), high fat (p-value=0.013), and both high fat and added sugars (p-value=0.017). Conclusions: Balanced nutrition behaviors are not significantly associated with nutritional status, while frequent consumption of discretionary foods is related to higher nutritional status. School-based nutrition interventions are needed to prevent overnutrition among adolescents.